Politeness Strategies in American: Movie Me Before You - Daniela Putri Tetenaung; Heri Heryono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze politeness strategies and also the factors that exist in the film from America "Me Before You". This study uses a qualitative descriptive method, the reason the researcher chooses this method is because the researcher wants to describe the situation that will be observed in the field more specifically, transparently, and in-depth. The film me before you is the source of the research data carried out. The data was studied using the theory of politeness strategies by Brown and Levinson (1987). Based on the research findings and results, there are four politeness strategies applied in the film, namely positive politeness strategies, negative politeness strategies, bald on-record strategies, and off-record strategies (indirect). The film In Me Before You uses a lot of positive politeness strategies, usually, the difference in the realization of politeness strategies used in films is influenced by several factors, namely the genre of the film, the age of the characters, and the closeness between the characters. after analyzing this film, the researcher got 120 data on politeness strategies, positive politeness 79 data, negative politeness 20 data, bald on-record 16 data, and off-record 5 data. So from these data, the researcher can conclude that the data is divided into 66% positive politeness, 17% negative politeness strategy, 13% bald on-record strategy, and 4% off-record strategy.